Analyzing the relationship between Industrialization and economic growth in Lesotho - Denis Nfor Yunil; Leseko S. Makhetha; Sylvester Lelimo (Cogent Economics & Finance, 2023)
The recent twin crises of the COVID-19 pandemic and the Russia-Ukraine war have caused global economic effects, with gross variation, across countries. Evidently, higher self-sufficient economies with more effective economic performances faired relatively better with these shocks. This calls for policymakers to revisit the drivers of growth with a specific interest in sectors or tools wherein they seem to have a comparative advantage. Industrialization becomes imperative for Lesotho and inspires this study's interest in analyzing its relationship with economic growth. Surprisingly, existing empirical literature shows heterogonous outcomes on the relationship between Industrialization and economic growth and sometimes contradicts the expected positive relationship in theories. This study employs the Auto Regressive Distributed Lag (ARDL) model, to test the dynamic effect of Industrialization on economic growth for a unique case study-Lesotho. Additionally, this study employs the nonlinear ARDL to investigate the existence of asymmetry in the model. The time span from 1981 to 2020. The findings show that industrial development has significantly impacted the economic growth of Lesotho in the short and long run. And there exists no significant asymmetry in the short and long run. This provides empirical evidence for policymakers to intensify efforts in promoting Industrialization in Lesotho.
Keywords: L50; O47; O55; 330; Africa; economic Growth; industrial development; industrial policy; Lesotho